The Development of Digital Books Based on Contextual Approach to Improve Mathematical Communication Skills at Mawaridussalam Class VII A.Y 2020/2021 - Putri Indah Lestari (Jurnal Fibonaci: Jurnal Pendidikan Matematika, 2022)
This research aims to obtain a digital book based on a contextual approach that is valid, practical, and effective, so as to improve students' mathematical communication skills on the material of perimeter and area of a rectangle.  The research instruments used were questionnaire and instrument validation sheets, lesson plans validation sheets, interactive teaching materials validation sheets, mathematical communication skills tests, and student and teacher response questionnaires to teaching materials.  After all instruments, lesson plans, and interactive teaching materials were declared valid by the validator, then readability tests and field trials were carried out.  The results of the study show that: (1) The digital book based on the contextual approach developed has met the criteria of validity based on the validator's assessment with an average validity of lesson plans of 87% in the very feasible category and the average validity of digital books is 90% for material and 88% for  media with very decent category;  (2) the contextual-based digital book developed has met the practicality criteria through: a) the results of the student response questionnaire to interactive teaching materials show the percentage of practicality of 79.9% in the very practical category;  b) the results of the teacher's response questionnaire to interactive teaching materials show the percentage of practicality of 89.01% with a very practical category;  (3) The developed contextual-based digital book meets the effective criteria with: a) classically 92% mastery of student learning;  b) more than 65% of students achieved 75% of the learning objectives for each indicator;  c) learning time is the same as ordinary learning in field trials and good student responses to the developed teaching materials.  Through the Gain test, it can be seen that the mathematical problem solving ability of students using digital books based on a contextual approach has increased by 0.74, meaning that it is in the high category